Rhetorical Robots: Making Robots More Effective Speakers Using Linguistic Cues of Expertise - Andrist, Sean; Spannan, Erin; Mutlu, Bilge (8th ACM/IEEE International Conference on Human-Robot Interaction (HRI ’13), 2013)
Robots hold great promise as informational assistants such as museum guides, information booth attendants, concierges, shopkeepers, and more. In such positions, people will expect them to be experts on their area of specialty. Not only will robots need to be experts, but they will also need to communicate their expertise effectively in order to raise trust and compliance with the information that they provide. This paper draws upon literature in psychology and linguistics to examine cues in speech that would help robots not only to provide expert knowledge, but also to deliver this knowledge effectively. To test the effectiveness of these cues, we conducted an experiment in which participants created a plan to tour a fictional city based on suggestions by two robots. We manipulated the landmark descriptions along two dimensions of expertise: practical knowledge and rhetorical ability. We then measured which locations the participants chose to include in the tour based on their descriptions. Our results showed that participants were strongly influenced by both practical knowledge and rhetorical ability; they included more landmarks described using expert linguistic cues than those described using simple facts. Even when the overall level of practical knowledge was high, an increase in rhetorical ability resulted in significant improvements. These results have implications for the development of effective dialogue strategies for informational robots.